Search in the Labor Market under Imperfectly Insurable Income Risk - Roca, Mauro (IMF Working Papers; Working Paper, 2009)
This paper develops a general equilibrium model with unemployment and noncooperative wage determination to analyze the importance of incomplete markets when risk-averse agents are subject to idiosyncratic employment shocks. A version of the model calibrated to the U.S. shows that market incompleteness affects individual behavior and aggregate conditions: it reduces wages and unemployment but increases vacancies. Additionally, the model explains the average level of unemployment insurance observed in the U.S. A key mechanism is the joint influence of imperfect insurance and risk aversion in the wage bargaining. The paper also proposes a novel solution to solve this heterogeneous-agent model.